Meaning of Forgiveness in the Naketi Rite Performed by the East Amanuban Community - Saetban, Difat; Snae, Deci; Freitas, Domingos (KnE Social Sciences, 2024)
Naketi Uab is a rite performed by the atoin meto community to prevent a problem from happening by involving certain parties. Another purpose of the Uab atoin meto naketi rite is to reorganize the damaged order of life of the community. The Uab naketi rite aims for openness, giving advice, as a means of communication, and also for restoring relationships with oneself, with others, and with God as the owner of life. Therefore, in this article, the author uses the theory of theological anthropology to examine and critically analyze human spiritual life, existence, and work in the culture of naketi Uab atoin meto for the restoration of communication relations. This research is a qualitative research with a phenomenological approach. Data were collected by way of observation, interviews, and documentation. The results show that naketi uab helps one to self-reflect, correct mistakes, and reconcile oneself with others and God as a form of relationship restoration. Keywords: naketi uab, theological anthropology, relations